Analisis Reduce Breakdown pada Mesin Bag Packaging - Basri, Muhammad Ikhsanudin; Apriananda, Redo (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
This study presents the analysis of downtime factors in the chain of a bag packaging machine. Through the use of a fishbone diagram, crucial factors were identified, including unstable gears, the absence of stoppers in the chain sprocket and outer chain, errors in chain setting by operators, lack of understanding and training regarding chain troubleshooting, suboptimal chain maintenance, and the absence of scheduled gear and chain replacements. To address these issues, improvement measures were implemented. The installation of stoppers in the sprocket and outer chain significantly reduced the risk of chain detachment and ensured stable rotation. Operator training and enhanced understanding improved chain troubleshooting and setting procedures. Optimal chain maintenance and scheduled gear and chain replacements contributed to the reduction of chain stiffness and gear damage. Over a three-month period following the implementation of the improvements, no downtime incidents related to the chain in the bag packaging machine were recorded, indicating the success of the implemented measures and an overall improvement in operational efficiency through the reduction of production disruptions caused by chain-related issues. Keywords—downtime, chain, bag packaging machine, fishbone diagram, improvement measures, operational efficiency.